Treatment of newly diagnosed paediatric acute lymphoblastic leukaemia on BFM-based chemotherapy protocol: Feasibility and outcome from a tertiary care center in India - Vipin Khandelwal; Dharma Choudhary; Sanjeev Kumar Sharma; Divya Doval; Anil Handoo; Tina Dadu; Nishit Gupta; Aditi Mittal; Rasika Setia (Elsevier, 2023)
Background: Data on outcomes in children with acute lymphoblastic leukaemia (ALL) who are on Berlin-Frankfurt-Munster (BFM)-based chemotherapy protocol is scarce from India. We share experience on the survival of children with ALL treated on the modified IC BFM 2002 protocol. Methods: Children (1-18 years) diagnosed with ALL between January 1, 2011 and January 1, 2021 at BLK-MAX Super Specialty Hospital were analyzed retrospectively. Patients were treated with modified IC BFM 2002 protocol. Data on the type of leukaemia, risk status, minimal residual disease (MRD), cytogenetic, and molecular genetics were collected. Disease free survival (DFS) and overall survival (OS) were calculated. Results: Hundred (88 B-cell, 12 T-cell) patients with ALL were evaluated. The median age at presentation was 6.5 years. According to the BFM risk stratification, 35 children were standard-risk, 45 were intermediate and 20 were high-risk. Bone marrow aspiration for MRD by flow cytometry on day 33 of induction chemotherapy was performed in 61 patients. One patient died on day 50 of induction. Day 78 MRD was performed in 60 patients. Day 78 MRD positivity was used for treatment escalation. There were 18 deaths. DFS as on 1st July 2023 for standard, intermediate and high-risk patients was 89%, 85% and 55% respectively. Overall survival in all risk groups was 82%. Conclusion: Treating childhood ALL with BFM-based chemotherapy protocol is feasible in developing countries without major modifications and with results comparable to those reported in Western literature.